Disperse Red 1 (textile dye) induces cytotoxic and genotoxic effects in mouse germ cells - Fernandes, Fabio Henrique [UNESP]; Bustos-Obregon, Eduardo; Favero Salvadori, Daisy Maria [UNESP] (Elsevier B.V., 2015)
Disperse Red 1 (DR1), which is widely used in the textile industry, is an azo dye that contributes to the toxicity and pollution of wastewater. To assess the toxic effects of DR1 on reproduction, sexually mature male mice (Mus musculus, strain CF-1) were orally (gavage) treated with single doses of the compound at 20, 100 and 500 mg/kg body weight. Testicular features and sperm parameters were evaluated 8.3, 16.6 and 24.9 days after treatments. In addition to testicular toxicity caused by the dye, the data clearly showed an increased frequency of sperm with abnormal morphology and decreased fertility. An increased amount of DNA damage was also detected in testis cells 16.6 and 24.9 days after treatments with 100 and 500 mg/kg. This study demonstrated the toxic and genotoxic effects of DR1, indicating the harmful activity of this dye on reproductive health. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Azo dye; Reproductive tract male; Environmental exposure; Fertility